Illicit Legislative Motivation As a Sufficient Condition for Unconstitutionality Under the Establishment Clause—A Case for Consideration: The Utah Firing Squad - Martin R. Gardner (Washington University Law Quarterly, 1979)
This Article tests the thesis that the religious motivation of legislators, apart from the religious effects of their legislation, is sometimes a legally and philosophically sufficient basis for striking down legislation under the establishment clause.
Keywords: Freedom of religion; Judicial review; Legislation; Prisons and prisoners; Penology